2023
DOI: 10.1097/rli.0000000000000947
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Agent Dose Reduction in MRI Utilizing a Generative Adversarial Network in an Exploratory Animal Study

Abstract: Objectives: The aim of this study is to use virtual contrast enhancement to reduce the amount of hepatobiliary gadolinium-based contrast agent in magnetic resonance imaging with generative adversarial networks (GANs) in a large animal model. Methods: With 20 healthy Göttingen minipigs, a total of 120 magnetic resonance imaging examinations were performed on 6 different occasions, 50% with reduced (low-dose; 0.005 mmol/kg, gadoxetate) and 50% standard dose (normaldose; 0.025 mmol/kg). These included arterial, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The only approaches to reduce the amount of contrast agents with true low-dose and normal-dose datasets via AI-based image-to-image conversion in dynamic contrast agent phases have been acquired in animal experiments to date. 3,14 These were able to show that the technology works in this setting, but they have 2 major drawbacks. It is hardly possible to show the diversity of human pathologies in animal experiments and thus validate the algorithm with these pathologies, and on the other hand, these algorithms, because they also learn anatomical information, are only limited to transfer to humans.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The only approaches to reduce the amount of contrast agents with true low-dose and normal-dose datasets via AI-based image-to-image conversion in dynamic contrast agent phases have been acquired in animal experiments to date. 3,14 These were able to show that the technology works in this setting, but they have 2 major drawbacks. It is hardly possible to show the diversity of human pathologies in animal experiments and thus validate the algorithm with these pathologies, and on the other hand, these algorithms, because they also learn anatomical information, are only limited to transfer to humans.…”
Section: Discussionmentioning
confidence: 97%
“…The use of AI as a new frontier of contrast media research has shown promising results in recent studies, both in the context of MRI and CT imaging. 1,3,6,14,28 The potential of AI in reducing contrast agent doses, as well as the feasibility of eliminating contrast agent use entirely, has been explored in several studies, 1,3,4,6,7,14,38 and new application areas for AI in contrast agent management have been proposed. 2 Yet, as the reviewed studies have shown, the diagnostic accuracy of AI-based approaches for contrast agent reduction may be dose dependent 10 or pathology dependent, particularly for small lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generative adversarial networks (GANs) [8] have gained a lot of attention in the last years due to their ability to generate realistic images. In the medical imaging field, they are often used for image-to-image translation problems, such as mapping magnetic resonance imaging (MRI) to computed tomography images [17,24], T1-weighted to T2-weighted MRI [14,22], or low-to high dose contrast enhanced MRIs [9,19]. Such approaches could potentially reduce healthcare costs and patient burden while maintaining or even improving the diagnostic value of a modality.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of this terminology added potentially to some confusion, as this entity and its associated symptoms (which include includes neurologic, cognitive, musculoskeletal, and other nonspecific complaints) were previously known by the terms gadolinium deposition disease and gadolinium storage condition. [26][27][28][29] Last in order but of great importance today (and potential impact upon the use of MR contrast media) is the use of artificial intelligence (AI) techniques in magnetic resonance and specifically their impact on contrast utilization-whether it be reduction of dose, [30][31][32][33] allowing new applications, 34 or the elimination of use in specific areas. [35][36][37] For the latter, it is still too early to come to any conclusions, and likely the answer is not straightforward.…”
mentioning
confidence: 99%